(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Based on the data gathered as well as the computation of the researchers using the Pearson r formula, the results show that there was a significant effect of poverty on crime rates, from the problems encountered by the respondents in terms of poverty up to the strategy made by the Barangay officials and measure of Barangay Officials In terms of controlling crime rates. The x -value is for poverty, with a total of 396, while the y-value is for crime rates, with a total of 5317. Using these two values, we computed using the Pearson r formula. The result is r = 0.158. Many of the respondents have problems with how they will earn money to sustain their needs, as well as problems in education in terms of school supplies and other expenses. Continuing the implementation of the local government unit of Barangay 163 Caloocan City in terms of pantawid pamilya program of DSWD and providing student assistance for their constituents may reduce the constantly increasing crime rates in the said barangay.